Customer relationship management strategies of selected resorts in Cavite: A pandemic situationer - Xavier Lawrence D. Mendoza; Rangie O. Espejon (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Customer relationship management (CRM) can be used to build relationships with customers and consistently acquire, retain, and create extra value for customers, even when a crisis like the COVID-19 pandemic has occurred. The study's primary objective was to determine and understand the customer relationship management strategies of selected resorts in Cavite during the pandemic. A descriptive-correlational research design was utilized in the study, and a purposive sampling technique was used in selecting targeted respondents. The researchers utilized a self-constructed survey questionnaire that 20 resort owners and managers answered in Dasmariñas City, General Trias City, Naic, and Tanza, Cavite. The result revealed that most of the respondents had operated their business for a long period of time, mostly as a sole proprietorship, and had a considerably small number of employees. The study found that the social media network was the most utilized customer relationship management strategy in the acquisition of potential customers. The marketing incentives were most used in retaining the customers. Lastly, most respondents utilized multiple channels supports to create extra value for customers. Considerably, there is no significant relationship between the business profile of the respondents and the perceived effectiveness of customer relationship management strategies except between the length of business operations and customer expansion. Despite the uncertainties brought by the pandemic to the hospitality and tourism industry, customer relationship management strategies aided the business sustainability of the resort businesses. In line with the existing new normal, this study recommended that resort firms should employ innovative strategies that are sensitive to customer trends.